COP29 in Azerbaijan: Some Considerations Based on Direct Observations of the Climate Events and Media Contents - Ibrahim Niftiyev (SSRN, 2024)
This discussion paper examines the key themes and findings from four major events and three pieces of media content on sustainable development, climate finance and environmental policy. Direct observation and structured notes were used as the main methods. The analysis begins with the webinar “Bridge Building in Baku,” which highlighted the need for improved quality and quantity of climate finance to support developing countries in their efforts to reduce carbon emissions. It then discusses the comparative perspectives on environmental issues between Azerbaijan and Türkiye, highlighting the need for renewable energy generation to offset environmental deficits. The paper also examines the event “COP29: Opportunities and Challenges for Climate Action,” which focused on international cooperation and learning from global best practices to address environmental challenges. Finally, the discussion at the event “Green and Circular Economy in the Turkic World” emphasizes the importance of reducing resource dependency and improving energy efficiency in Turkish states. Policy suggestions include creating financial incentives for green technologies, improving public education on sustainability and promoting international cooperation to effectively address environmental challenges. This paper aims to map the intellectual landscape of climate finance and sustainable development and provides insights for policymakers and stakeholders involved in global climate action based primarily on COP29.
Keywords: Q20; Q28; Q54; Q57; Q58; 330; Azerbaijani economy; climate events; climate change; COP29; renewable energy; sustainable development